Institutional Challenges of university teacher training - Inmaculada Torra Bitlloch; María Dolores Màrquez Cebrian; Teresa Pagès Costas; Pau Solà Ysuar; Rafael García Campos; Fidel Molina Luque; Àngel-Pío González Soto; Albert Sangrà Morer (Universitat Politècnica de València, 2013)
The units or training centers (ICE IDES CQUID, ELC) of the eight public universities in Catalonia, constituted as Interuniversity Group on Teacher Education (GIFD), are currently undergoing a reformulation process concerning the training activities and plans being offered to university teachers, in order to facilitate the development of their teaching activity. The rethinking of their actions is born from a common interest linking the quality of university teachers' training with coherent approaches in the European Higher Education Area (EHEA). This interest and concern has led the group to conduct a research study with the objective of establishing a set of standard teaching skills for the faculty staff to master, with the purpose of successfully undertaking the development of the new degree courses in line with the directives of the European Higher Education Area. This paper contains a thorough examination and analysis regarding the main features that activities and training programs aimed at teachers should include, in order to facilitate the performance of the teaching activity itself, by focusing at the work of training units or training centers, at the academic institutions where they belong, and at the related agencies, and by requesting them to update their educational tasks in order to meet the new requirements that the role of teachers demand. The aim of this work is to stimulate thought and to generate a debate on the direction that university teachers' training must follow, not only as a strategic element of the institution, but also contributing to achieve the quality objectives to which universities have committed themselves in the process of validating the new degrees.